2012
DOI: 10.2147/ijn.s28101
|View full text |Cite
|
Sign up to set email alerts
|

Nano-TiO2/PEEK bioactive composite as a bone substitute material: in vitro and in vivo studies

Abstract: Background: Compared with titanium (Ti) and other metal implant materials, poly(ether-ether ketone) (PEEK) shows outstanding biomechanical properties. A number of studies have also reported attractive bioactivity for nano-TiO 2 (n-TiO 2 ). Methods: In this study, n-TiO 2 /PEEK nanocomposites were prepared, taking advantage of the unique properties of both PEEK polymer and n-TiO 2 . The in vitro and in vivo bioactivity of these nanocomposites was assessed against a PEEK polymer control. The effect of surface mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…Previous studies have reported that PEEK material exhibits extremely limited osteoconductive properties, unlike titanium. Therefore, a significant amount of research has been conducted to increase the bioactivity of PEEK implants (25). Primary of these are studies of surface roughening.…”
Section: Peek Implantsmentioning
confidence: 99%
“…Previous studies have reported that PEEK material exhibits extremely limited osteoconductive properties, unlike titanium. Therefore, a significant amount of research has been conducted to increase the bioactivity of PEEK implants (25). Primary of these are studies of surface roughening.…”
Section: Peek Implantsmentioning
confidence: 99%
“…Nowadays, alloy is used for its superior corrosion resistance, and different types of bearing surfaces are available 49,50 . Ti particles released from Ti bulk implant or composites was confirmed by studies, and it was inevitable to apply Ti as a biomaterial, considering its outstanding mechanical property 1,2,13,14,16,17,22 . However, little is known about the interaction existing in different materials 50 .…”
Section: Discussionmentioning
confidence: 96%
“…In particle disease, peri-implant osteolysis which is caused by wear particles remains the main complication for implant failure after the surgical [5][6][7][8] . Although the development of materials (Metal, Polyethylene, Polymethylmethacrylate, and Ceramic) undergone a marvelous evolution over the past half-century, yet none can be considered to be absolutely perfect [9][10][11][12][13] . However, the biological interaction between different types of particles was hardly studied.…”
mentioning
confidence: 99%
See 2 more Smart Citations